2013
DOI: 10.1016/j.orcp.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic prepro-orexin mRNA level is inversely correlated to the non-rapid eye movement sleep level in high-fat diet-induced obese mice

Abstract: Orexins are hypothalamic neuropeptides, which play important roles in the regulation and maintenance of sleep/wakefulness states and energy homeostasis. To evaluate whether alterations in orexin system is associated with the sleep/wakefulness abnormalities observed in obesity, we examined the mRNA expression of prepro-orexin, orexin receptor type 1, (orexin 1r), and orexin receptor type 2 (oxexin 2r) in the hypothalamus in mice fed with a normal diet (ND) and high-fat diet (HFD)-induced obese mice. We also com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…; Tanno et al . ). In keeping with this, the present study found that LTD was no longer induced after 4 weeks of WD.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Tanno et al . ). In keeping with this, the present study found that LTD was no longer induced after 4 weeks of WD.…”
Section: Discussionmentioning
confidence: 97%
“…; Tanno et al . ). Thus, the regulation of the orexin system may change over the course of high‐fat diet feeding.…”
Section: Introductionmentioning
confidence: 97%
“…Orexin (or hypocretin) signaling is necessary for wake bout stability, because disruption of this pathway induces narcolepsy. 32,33 Previous reports have found that HFD reduces prepro-orexin levels 34 and potentially reduces the number of orexin immunopositive neurons in the lateral hypothalamus. 35 Therefore, we predict that orexin signaling partially mediates the diet-induced sleep/ wake effects.…”
Section: Discussionmentioning
confidence: 97%
“…It is known that diet among overweight and obese individuals is characterized by a larger proportion of fat in total energy consumption [12]. One study has shown that chronic high fat feeding reduces prepro-orexin level in hypothalamus in obese mice [30]. Since orexin is an important neuropepitide for maintaining wakefulness and regulating energy balance, we hypothesize that by reducing total energy intake, orexin signaling in the hypothalamus is strengthened, which induces more stable wakefulness and less sleep duration during the daytime.…”
Section: Discussionmentioning
confidence: 99%